The Effect of Design, Packaging, and Promotion on Consumer Purchase Intention at Tiya Fashion Store - Aditiya, Cristian; Nurrahman, Adithia; Dedu, May; Agustina, Agustina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study had the aim to examine the effect of product design, packaging, along with promotion on consumer purchase intention at the Tiya Fashion online store. A quantitative approach was used with data processing using the PLS-SEM method. The findings revealed that all independent variables significantly affect purchase intention. Among the three variables, promotion is the dominant factor driving consumers’ purchasing decisions, while design and packaging have lower contributions. The research model is considered appropriate and free from multicollinearity issues. These findings indicate the importance of strengthening promotional strategies, particularly through digital channels, as an effective step to increase sales conversion. This study provides strategic recommendations for online fashion business actors, especially MSMEs, in designing more targeted and impactful marketing approaches.